Foreign Policy as Instrument of Elite Preservation - Zimbabwe's foreign policy within the Southern African Development Community (SADC), 2000 - 2017 - Zondi, Siphamandla (University of Pretoria, 2022)
Thesis (PhD (International Relations))--University of Pretoria, 2022.